2020
DOI: 10.1111/1759-7714.13763
|View full text |Cite
|
Sign up to set email alerts
|

Phase II open‐label multicenter study to assess the antitumor activity of afatinib in lung cancer patients with activating epidermal growth factor receptor mutation from circulating tumor DNA: Liquid‐Lung‐A

Abstract: Background Mutation analysis of circulating tumor DNA (ctDNA) is used for diagnosing lung cancer. This trial aimed to assess the efficacy of afatinib in treatment‐naïve patients with lung cancer harboring epidermal growth factor receptor mutations (EGFRm, exon 19 deletions or exon 21 point mutations) detected based on ctDNA. Methods The primary objective was the objective response rate (ORR) in the response evaluable (RE) population. EGFRm analysis of ctDNA was performed using PANA Mutype. Of the 331 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Accurate molecular typing is the basis of this precise treatment; however, qualified tumor tissue specimens cannot be obtained from every patient, so liquid biopsy was developed. Many studies have prospectively verified the high specificity (92–100%) and positive predictive value (94.0–98.6%) of ctDNA-based EGFR mutation detection using tissues as a reference [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and these two metrics have also been consistent in guiding the targeted therapy of NSCLC [ 30 , 31 , 34 , 35 ]. Recently, research on ctDNA-based next-generation sequencing (NGS) has demonstrated potential clinical utility [ 36 , 37 , 38 , 39 ].…”
Section: Plasma Ctdna-based Egfr Mutations Can Guide Targeted Therapy...mentioning
confidence: 98%
See 2 more Smart Citations
“…Accurate molecular typing is the basis of this precise treatment; however, qualified tumor tissue specimens cannot be obtained from every patient, so liquid biopsy was developed. Many studies have prospectively verified the high specificity (92–100%) and positive predictive value (94.0–98.6%) of ctDNA-based EGFR mutation detection using tissues as a reference [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and these two metrics have also been consistent in guiding the targeted therapy of NSCLC [ 30 , 31 , 34 , 35 ]. Recently, research on ctDNA-based next-generation sequencing (NGS) has demonstrated potential clinical utility [ 36 , 37 , 38 , 39 ].…”
Section: Plasma Ctdna-based Egfr Mutations Can Guide Targeted Therapy...mentioning
confidence: 98%
“…Table 1 presents data on the association between plasma ctDNA/cfDNA EGFR mutations and the efficacy and prognosis of targeted therapy in NSCLC patients [ 28 , 30 , 31 , 32 , 33 , 34 , 35 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The BENEFIT trial prospectively demonstrated the feasibility of using liquid biopsy to guide the efficacy of first-line EGFR-TKI therapy for the first time.…”
Section: Plasma Ctdna-based Egfr Mutations Can Guide Targeted Therapy...mentioning
confidence: 99%
See 1 more Smart Citation